Transmission dynamics of drug-resistant tuberculosis in Ningbo, China: an epidemiological and genomic analysis - Che, Yang; Li, Xiangchen; Chen, Tong; Lu, Yewei; Sang, Guoxin; Gao, Junli; Gao, Junshun; Liu, Zhengwei; He, Tianfeng; Chen, Yi (Frontiers in Cellular and Infection Microbiology, 2024)
Background: Tuberculosis (TB), particularly drug-resistant TB (DR-TB), remains a significant public health concern in Ningbo, China. Understanding its molecular epidemiology and spatial distribution is paramount for effective control.Methods: From December 24, 2020, to March 12, 2023, we collected clinical Mycobacterium tuberculosis (MTB) strains in Ningbo, with whole-genome sequencing performed on 130 MTB strains. We analyzed DR-related gene mutations, conducted phylogenetic and phylodynamic analyses, identified recent transmission clusters, and assessed spatial distribution.Results: Among 130 DR-TB cases, 41% were MDR-TB, 3536% pre-XDR-TB, 19% RR-TB, and 3% HR-TB. The phylogenetic tree showed that 90% of strains were Lineage 2 (Beijing genotype)Lineage 2 Beijing family strains dominated at 90%, while remaining 10% were Lineage 4 (Euro-American genotype). Phylodynamic analysis indicated two notable expansions in the effective population size of DR-TB in the last century, reaching a peak of 10,000 during 1938-1944 and 1978-1981, and subsequently declining to 1,000 between 2010 and 2019. The spatial analysis identified hotspots of DR-TB in Ningbo's northern region, particularly in traditional urban centers. 31 (24%) of the DR-TB cases were grouped into 7 recent transmission clusters with a large outbreak cluster containing 15 pre-XDR-TB patients.Epidemiological analyses suggested a higher risk of recent DR-TB transmission among young adult patients who frequently visited Internet cafes, game rooms, and factories.Our study provides comprehensive insights into the epidemiology and genetics of DR-TB in Ningbo. The presence of genomic clusters highlights recent transmission events, indicating the need for targeted interventions. These findings are vital for informing TB control strategies in Ningbo and similar settings.